The Lucky Leaf Casino: A Retroscape in Cynthia Shearer’s The Celestial Jukebox - Altindis, Huseyin (Hungarian Journal of English and American Studies, 2020)
Representations of the American South and the southern sense of space have been changing rapidly due to transnational effects of colonialism, globalization, and the rise of technologies. Due to such factors, unprecedented numbers of people now travel to more distant and less visited places. One consequence of such changes is that place and spatiality represent multicultural and global perceptions and experiences rather than being uniquely and distinctively local. Market economies exploit the space and create retroscapes to serve the economic aims of various industries. Within this context, drawing on the aesthetics of space, memory, and nostalgia, the paper focuses on the Lucky Leaf Casino in Cynthia Shearer’s The Celestial Jukebox to discuss how the text challenges and problematizes plantation nostalgia and labor exploitation through which power structures continue to restrict, disrupt, and exploit space, people, and history. (HA)